Mysticism Unbound: An Interpretative Reading of Jeffrey J. Kripal's Contribution to the Contemporary Study of Mysticism - Kelly, Jason James (Université d'Ottawa / University of Ottawa, 2011)
This thesis examines the relationship between human sexuality and “the mystical” in the work of Jeffrey J. Kripal. I claim that Kripal presents a nondualistic understanding of the relationship between human sexuality and “the mystical” that contests the conventional distinction between body and “soul.” In particular, Kripal’s two central concepts – “the erotic” and “the enlightenment of the body” – suggest that embodiment shapes our understanding of “the mystical.” By demonstrating the psychoanalytic, hermeneutical, and comparative significance of the relationship between human sexuality and “the mystical,” Kripal’s model calls attention to the crucial role that body, gender, and sexual orientation play in both the historical and contemporary study of mysticism. The point of my research is to show that Kripal’s approach signals a new way of studying “the mystical” in terms of “mystical humanism,” which draws on both Eastern and Western philosophies to construct a critical, non-reductive appreciation for the transformative and ultimately emancipatory potential of certain mystical states of consciousness.
Keywords: Mysticism; Erotic; Body; Psychoanalysis